Revisiting the Doctrine of Necessity: Judicial Interpretation in Pakistan and the April 2022 Crisis - Hamza Bin Anees; Khan, Jawad; Hamid, Aleena (ACADEMIA International Journal for Social Sciences, 2025)
The creation of Pakistan on August 14, 1947, was the realization of a separate homeland for Muslims, yet from its inception the country has remained entangled in crises, both political and constitutional. The internal structure of Pakistan was destabilized not only by socio-political challenges but also by repeated unconstitutional interventions carried out by usurpers in power. The Constitutions of 1956, 1962, and 1973 were frequently suspended and violated, and such extra-constitutional measures were legitimized by courts under the doctrine of state necessity. This judicial validation of coups and unconstitutional actions created a dangerous precedent that undermined constitutionalism, rule of law, and democratic consolidation for decades. The doctrine of necessity provided a legal cover for usurpation of power and perpetuated a cycle of instability, weakening institutions and eroding public trust in judicial impartiality. However, the political crisis of April 2022 marked a significant departure from this troubled legacy. When the government of Prime Minister Imran Khan was removed through a constitutional process, the Supreme Court of Pakistan was called upon to adjudicate the matter. Exercising its suo motu jurisdiction, the Court annulled the unconstitutional dissolution of the National Assembly and restored Parliament, thereby ensuring continuity of democratic governance. This research examines the historical evolution of the doctrine of necessity in Pakistan, its legitimizing role in constitutional breakdowns, and the precedents it established. It then critically analyzes the events of April 2022, where the Supreme Court rejected the misuse of necessity and reinforced constitutional supremacy. The decision is hailed as a landmark development in Pakistan’s judicial history, symbolizing the burial of the doctrine of necessity and laying the foundation for constitutional harmony and democratic resilience in the future.